Pemanfaatan Tik Sebagai Sumber Dan Media Pembelajaran Di Sekolah - Sodiq Anshori (Penerbit STKIP PGRI Bangkalan, 2018)
The development of information and communication technologies advance so quickly penetrated allthese sectors of life. The development of Information and Communication Technology (ICT) israpidly increasing.The need for a concept and mechanism of learning (education) -based IT isinevitable. This concept becomes known as e-learning brings the influence of conventional educationtransformation process into a digital form, both contents (contents) and the system. Currently, elearning concept has been widely accepted by the world community, as evidenced by the widespreadimplementation of e-learning, especially in educational institutions (schools, training, anduniversity).This system is an efficient and effective system for using only an Internet connection will be realized alearning. Sumber process of learning in this digital era known as OER (Open EducationalResources) that any of the assets or learning resources (print / electronic) that can be accessed,download and use free and open to the public (anyone) for the sake of learning and research.Without the need to file a written permission to the creator/publisher (copyright) (Dholakia, king, &baraniuk, 2006; OECD, 2007). Learning resources are utilized and developed in Higher EducationDistance (Newspapers) as an online learning media (online media).